Clinical Outcome of Patients with Glaucoma undergoing Peripheral Iridectomy and Phacoemulsification: Long-Term Follow-Up Case Series Study (Ukrainian Journal of Ophthalmology, 2025)
Purpose. Primary angle-closure glaucoma (PACG) is a leading cause of irreversible blindness globally, with elevated intraocular pressure (IOP) as a critical risk factor. Surgical interventions, such as phacoemulsification (PE) with intraocular lens (IOL) implantation and peripheral iridectomy (PI), have shown efficacy in IOP control and visual restoration. This study evaluates the long-term clinical outcomes of PE and IOL combined with PI in PACG management.Material and Method. A retrospective case series was conducted involving 13 PACG patients (22 eyes) who underwent PE and IOL or PE and IOL with PI between 2018 and 2023. Data were collected from medical records, including pre- and postoperative IOP and best corrected visual acuity (BCVA). Follow-up assessments were performed on Day 1, Month 1, Month 3, Month 6, and annually up to Year 4.Result. Both surgical approaches effectively reduced intraocular pressure (IOP) and improved best corrected visual acuity (BCVA). The addition of PI showed a more consistent early postoperative IOP reduction (100% of eyes decreased from baseline to day 1 and month 6) and maintained lower IOP in the majority of cases over long-term follow-up. BCVA improved in all eyes except those with baseline no light perception (LP-), with the PE + PI group demonstrating greater and more sustained visual improvement. However, some cases in the PE-only group experienced IOP elevation or vision decline during follow-up.Conclusions. PE and IOL, particularly when combined with PI, provides superiority in early IOP control and sustained BCVA gain. However, irreversible optic nerve damage at baseline remains a limiting factor for visual recovery.
Keywords: visual acuity; intraocular pressure; angle-closure glaucoma; phacoemulsification; intraocular lens implantation; iridectomy